Nilai-Nilai Pendidikan Islam pada Pasal “Lelad Ain Fo Mahiling” dalam Hukum Adat Larvul Ngabal pada Masyarakat Kepulauan Kei Provinsi Maluku - Difinubun, Mahdi Mardani; Nur, Indria; Sudirman, Sudirman (Jurnal Ragam Pengabdian, 2026)
This study aims to identify the Islamic educational values ​​contained in the article "Lelad Ain Fo Mahiling" of the Larvul Ngabal customary law, analyze its relevance in character formation of the Kei community, and examine the impact of its implementation in facing contemporary socio-religious challenges. The study uses a qualitative approach with a phenomenological design to understand the meaning of Islamic educational values ​​that live in the traditional traditions and religious life of the Kei Islands community. Data were obtained through in-depth interviews, participatory observation, and documentation studies involving traditional leaders, religious leaders, Islamic Religious Education teachers, women, and the younger generation. Data analysis was carried out descriptively qualitatively through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the article "Lelad Ain Fo Mahiling" which means "do not harm others" contains Islamic educational values ​​in the form of faith, worship, and social morals that are integrated into the lives of the Kei community. The value of faith is reflected in the belief in Allah SWT's supervision of every human action, the value of worship is realized through cooperation, mutual assistance, and social responsibility, while the value of morals is seen in attitudes of mutual respect, honesty, self-control, and deliberation. The application of these values ​​contributes to strengthening moral awareness and social harmony, so that it can become the foundation for developing Islamic character education based on relevant and sustainable local wisdom.